2016
DOI: 10.3310/hta20840
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced invitation methods and uptake of health checks in primary care: randomised controlled trial and cohort study using electronic health records

Abstract: BackgroundA national programme of health checks to identify risk of cardiovascular disease (CVD) is being rolled out but is encountering difficulties because of low uptake.ObjectiveTo evaluate the effectiveness of an enhanced invitation method using the question–behaviour effect (QBE), with or without the offer of a financial incentive to return the QBE questionnaire, at increasing the uptake of health checks. The research went on to evaluate the reasons for the low uptake of invitations and compare the case m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 63 publications
(113 reference statements)
2
37
0
Order By: Relevance
“…Overall uptake of health checks in response to an invitation was low and our results do not exclude the possibility of an effect of the intervention in the context of higher overall uptake. In the present context, low health check uptake might be explained by service organization and delivery factors that impede the ease with which people can obtain a health check [28].…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Overall uptake of health checks in response to an invitation was low and our results do not exclude the possibility of an effect of the intervention in the context of higher overall uptake. In the present context, low health check uptake might be explained by service organization and delivery factors that impede the ease with which people can obtain a health check [28].…”
Section: Discussionmentioning
confidence: 92%
“…Trial practices tended to have larger patient list sizes than non-trial practices but showed similar levels of achievement of clinical performance metrics. Trial practice populations were similar with respect to social and material deprivation and proportion of non-White participants to the entire populations of the two boroughs [28]. Each practice participated in the trial for a minimum of 12 months to allow for seasonal variation in uptake of health checks.…”
Section: General Practice and Individual Participant Recruitmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Various methods aimed at increasing uptake of invitations to NHS Health Checks have been investigated. A review of evidence found modified invitation letters and use of text messages to be promising methods for the general eligible population . However, it is of particular interest to understand how to increase uptake amongst groups who may be at higher risk of cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%